2013
DOI: 10.1167/iovs.12-11471
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Development and Feasibility of Choroidal Imaging in the Preterm and Term Infants Utilizing SD-OCT

Abstract: PURPOSE. To determine whether choroidal imaging is feasible in preterm and term infants using an 840-nm portable spectral domain optical coherence tomography (SD-OCT) system without the use of enhanced-depth imaging techniques and to assess choroidal development by comparing choroidal thickness of preterm infants, term infants, and adults.METHODS. SD-OCT images were obtained from 86 preterm infants, 59 term infants, and nine adults using a portable SD-OCT system plus nine adults using a tabletop system. An unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 43 publications
3
53
1
1
Order By: Relevance
“…The development of a handheld SD-OCT has enabled pediatric practitioners to acquire high resolution images of the circumpapillary RNFL and macula in neonates, infants and young children. [13][14][15][16][17][18][19][20][21][22][23][24] While neonates and infants can be imaged while awake, the portability of the handheld OCT permits acquisition in toddlers and young children during sedation.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a handheld SD-OCT has enabled pediatric practitioners to acquire high resolution images of the circumpapillary RNFL and macula in neonates, infants and young children. [13][14][15][16][17][18][19][20][21][22][23][24] While neonates and infants can be imaged while awake, the portability of the handheld OCT permits acquisition in toddlers and young children during sedation.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this technology will provide a compact and cost-effective solution for high SNR, motion-corrected imaging of patients that are supine, under anesthesia, or unable to position. These include infants with variety of retinal diseases such as retinopathy of prematurity [12, 35,36] albinism [37], nystagmus [38], Shaken baby syndrome [15], and for imaging young children.…”
Section: Resultsmentioning
confidence: 99%
“…11 Robb showed the ability of RPE to stimulate choroidal vasculature development. 12 Other study that corroborates the relevance of RPE in choroid development, revealed absence of choriocapillaris in absence of VEGF expression by RPE.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to lower oxygen levels, choroidal vasculature continues to develop, and the choroid becomes thicker and closer to choroid of normal infants. 11 Lower expression of VEGF RPE and high levels of oxygen could be the reason for a thinner choroid in patients with ROP comparing with preterm children.…”
Section: Discussionmentioning
confidence: 99%